2016
DOI: 10.1007/s00125-016-3899-2
|View full text |Cite
|
Sign up to set email alerts
|

Improved glucose regulation in type 2 diabetic patients with DPP-4 inhibitors: focus on alpha and beta cell function and lipid metabolism

Abstract: Inhibition of dipeptidyl peptidase-4 (DPP-4) is an established glucose-lowering strategy for the management of type 2 diabetes mellitus. DPP-4 inhibitors reduce both fasting and postprandial plasma glucose levels, resulting in reduced HbA 1c with low risk for hypoglycaemia and weight gain. They act primarily by preventing inactivation of the incretin hormones glucose-dependent insulinotropic polypeptide and glucagon-like peptide-1, thereby prolonging the enhanced endogenous levels of these hormones after meal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
82
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(97 citation statements)
references
References 103 publications
(64 reference statements)
9
82
1
1
Order By: Relevance
“…The enhancement of beta cell function by vildagliptin is well established [11] and shown here also when beta cell mass is severely depleted. Habener and colleagues have demonstrated that beta cell damage or stress up-regulates islet SDF-1 mRNA expression and secretion of SDF-1 from beta cells (8).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The enhancement of beta cell function by vildagliptin is well established [11] and shown here also when beta cell mass is severely depleted. Habener and colleagues have demonstrated that beta cell damage or stress up-regulates islet SDF-1 mRNA expression and secretion of SDF-1 from beta cells (8).…”
Section: Discussionsupporting
confidence: 61%
“…This would suggest that actions of vildagliptin are dependent on augmentation of extra islet effects [11], which, however, requires further mechanistic studies.…”
Section: Discussionmentioning
confidence: 99%
“…Dipeptidyl peptidase-4 (DPP-4) inhibitors are a new class of oral antidiabetic drugs for treatment of T2DM 3. Physiologically, DPP-4 inhibitors increase the availability of active glucagon-like peptide-1 (GLP-1) and glucose-dependent insulinotropic polypeptide (GIP) in plasma, which in turn, improves the sensitivity of pancreatic β- and α-cells to glucose 3,4…”
Section: Introductionmentioning
confidence: 99%
“…GLP-1 regulates blood glucose mainly by acting on pancreatic islet cells via mechanisms that include the stimulation of insulin secretion [1]. GLP-1 preserves beta cell by inhibiting apoptosis, although increase in beta cell mass has not been observed with any GLP-1 based therapy in man, even in rodents [4]. GLP-1 also inhibits glucagon secretion and suppresses gastric emptying, gastric secretion, and exocrine pancreatic secretion.…”
Section: Introductionmentioning
confidence: 99%